Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702203
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Participatory Production

Abstract: We conducted a study to explore the values and qualities of 'grassroots documentaries', framed around the production of two parallel documentary films with a London-based opera company. A team of professional filmmakers produced one film and the other was an exploratory form of grassroots documentary. We studied the different production activities through observations, interviews and a reflective workshop at the end of the study and evaluated the resulting films. Our analysis reveals critical insights that cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 20 publications
1
6
0
1
Order By: Relevance
“…This was not due to a lack of creativity; rather it resulted from a lack of familiarity with specialist vocabulary, and a lack of specific technical skills. The fact that most of the highly motivated, genre-literate, creative artists we worked with required high levels of support to edit a short video in a highly conventional genre corroborates evidence in other studies [18,11] that have found untrained users disengage with video at the editing stage. Video editing is now a well-known barrier to high quality media making by non-professionals.…”
Section: De-isolating 'Production'supporting
confidence: 82%
“…This was not due to a lack of creativity; rather it resulted from a lack of familiarity with specialist vocabulary, and a lack of specific technical skills. The fact that most of the highly motivated, genre-literate, creative artists we worked with required high levels of support to edit a short video in a highly conventional genre corroborates evidence in other studies [18,11] that have found untrained users disengage with video at the editing stage. Video editing is now a well-known barrier to high quality media making by non-professionals.…”
Section: De-isolating 'Production'supporting
confidence: 82%
“…Eu-roPARC's RAVE [20] and WAVE [48] systems, and collaborative production practices, e.g. including collaborative viewing experiences [21], and documentary production within grassroots movements [23]. Together with methodological frameworks for collaborative authoring [40,9], they offer insights into the different video communication and production practices and further our understanding of video editing practice.…”
Section: Research On Video Interactionmentioning
confidence: 99%
“…The argument follows that non-linear narratives are better suited to polyvocality, since they attenuate the distortions of single authors (whether they are outsiders or insiders) into a more balanced, overall impression. This argument is reflected in recent literature about i-Docs, which suggests they are well-suited to facilitating nuanced representations of heterogeneous communities and the diverse qualities of user-generated media [31]. However, most agree that enabling participation in i-Docs is challenging, and its potential is under-realized [26,1,49].…”
Section: The Problem With Documentariesmentioning
confidence: 99%
“…It is widely acknowledged that documentary can be a positive force for enabling public discourses and facilitating social change [43,46] and it is an area of burgeoning interest within HCI [4,17,31]. The documentary scholar Mandy Rose has recently suggested ways that documentary could be 'more like participatory design' [56], but there is a mutual value in bridging the disciplines of documentary scholarship and HCI.…”
Section: Introductionmentioning
confidence: 99%